Bacterial Adhesion to Soil Contaminants in the Presence of Surfactants - Stelmack, Patricia L. (American Society for Microbiology, 1999)
It has been proposed that addition of surfactants to contaminated soil enhances the solubility of target compounds; however, surfactants may simultaneously reduce the adhesion of bacteria to hydrophobic surfaces. If the latter mechanism is important for the biodegradation of virtually insoluble contaminants, then the use of surfactants may not be beneficial. The adhesion of a Mycobacterium strain and a Pseudomonas strain, isolated from a creosote-contaminated soil, to the surfaces of highly viscous non-aqueous-phase liquids (NAPLs) was measured. The NAPLs were organic material extracted from soils from two creosote-contaminated sites and two petroleum-contaminated sites. Cells suspended in media with and without surfactant were placed in test tubes coated with an NAPL, and the percentages of cells that adhered to the surface of the NAPL in the presence and absence of surfactant were compared by measuring optical density. Test tubes without NAPLs were used as controls. The presence of either Triton X-100 or Dowfax 8390 at a concentration that was one-half the critical micelle concentration (CMC) inhibited adhesion of both species of bacteria to the NAPLs. Both surfactants, when added at concentrations that were one-half the CMCs to test tubes containing previously adhered bacteria, also promoted the removal of the cells from the surfaces of the NAPL-coated test tubes. Neither surfactant was toxic to the bacteria. Further investigation showed that a low concentration of surfactant also inhibited the growth of both species on anthracene, indicating that the presence of a surfactant resulted in a reduction in the uptake of the solid carbon source.